Using Bourdieu to think about the Tertiary Learning Advice Consultation - Roberts, Mary; Reid, Kirsten (Journal of Academic Language and Learning, 2014)
The tertiary learning advice consultation (TLAC) is a relatively recent cultural event. As such, it lacks a generally recognised cultural framework, and it is under-theorised with regard to relevant pedagogical literature. We argue that this lack of clarity means that the nature of the TLAC is not particularly well understood by university administrators, teachers, and students. One significant effect of this is that the consultation can be seen as merely a site of skill transmission.This paper uses Bourdieu’s (1998) concepts of cultural field, habitus, the rules of the game and reflexivity to argue that framing the TLAC as a matter of skill transmission and little else fails to recognise what is at stake in the TLAC, and the ways in which those consultations can help students acquire an appropriate academic habitus and literacy. We also argue that the TLAC is often concerned with the “discursive formation” of reflexivity (Bourdieu & Wacquant, 1992), and that even tertiary learning advisors (TLAs) themselves could benefit from thinking about the TLAC in a wider and more developed historical and theoretical context. In order to establish an objective understanding of the demands and practices of the field, we examined university websites and research on the attributes of successful students. We also looked at data from TLACs with international students to help us understand how these demands and practices play out in the lives of individuals. We argue that in order for students to take on the academic habitus and to ‘succeed’ within the academic field, they need not only to develop that habitus and learn the rules of the field, but also be able to articulate the relationship between their personal trajectory, their habitus and the rules and demands of the field.